The Role of Behavioral Accounting Aspects in Organization Decentralization and Performance Evaluation in Companies in Indonesia - Anggiria, Kristanti Srika; Trisnaningsih, Sri (Asian Journal of Management Analytics, 2024)
Organizational decentralization can increase organizational efficiency and effectiveness, but it can also cause several problems. This research aims to analyze aspects of behavioral accounting that are relevant to organizational decentralization and performance evaluation. This research uses a literature review study technique. The method for collecting data in this research is through literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation, and conclusion. The research results show that the behavioral accounting aspect of decentralization and performance evaluation is a concept that includes human resource management, budget control, and decision making in organizations. Aspects of behavioral accounting in decentralization and performance evaluation include tight budget control, decision-making, employee performance, motivation, decision-making, leadership, reward systems, satisfaction, conflict, and pressure.